A Feminist Ethics of Abortion - Anna Réz (Elpis)
In feminist philosophy, there is a silent but consistent recurrence of criticisms regarding the mainstream, “liberal” defense of the right to abortion, most prominently exemplified by Judith Jarvis Thomson’s seminal paper “A Defense of Abortion”. In this paper, I explore the feminist proposals of Alison M. Jaggar (1975) and Sally Markowitz (1990) and examine, in light of these, the prospects of a particularly feminist ethics of abortion. I argue that although feminist theorists are right to say that defenses based on bodily autonomy set the wrong agenda for public discourse, thus contributing to a misleading and uninformed debate, Thomsonian arguments still have considerable advantages, both in philosophy and in the public discourse. In particular, while Thomsonian accounts can successfully sidestep the conflict between the mother’s and the fetus’s rights, currently available feminist proposals can meaningfully transform but cannot eliminate this problem.